Acute Stress Suppresses Synaptic Inhibition and Increases Anxiety via Endocannabinoid Release in the Basolateral Amygdala - Di, Shi; Itoga, Christy A; Fisher, Marc O; Solomonow, Jonathan; Roltsch, Emily A; Gilpin, Nicholas W; Tasker, Jeffrey G (The Journal of neuroscience, 2016)
Stress and glucocorticoids stimulate the rapid mobilization of endocannabinoids in the basolateral amygdala (BLA). Cannabinoid receptors in the BLA contribute to anxiogenesis and fear-memory formation. We tested for rapid glucocorticoid-induced endocannabinoid regulation of synaptic inhibition in the rat BLA. Glucocorticoid application to amygdala slices elicited a rapid, nonreversible suppression of spontaneous, but not evoked, GABAergic synaptic currents in BLA principal neurons; the effect was also seen with a membrane-impermeant glucocorticoid, but not with intracellular glucocorticoid application, implicating a membrane-associated glucocorticoid receptor. The glucocorticoid suppression of GABA currents was not blocked by antagonists of nuclear corticosteroid receptors, or by inhibitors of gene transcription or protein synthesis, but was blocked by inhibiting postsynaptic G-protein activity, suggesting a postsynaptic nongenomic steroid signaling mechanism that stimulates the release of a retrograde messenger. The rapid glucocorticoid-induced suppression of inhibition was prevented by blocking CB1 receptors and 2-arachidonoylglycerol (2-AG) synthesis, and it was mimicked and occluded by CB1 receptor agonists, indicating it was mediated by the retrograde release of the endocannabinoid 2-AG. The rapid glucocorticoid effect in BLA neurons in vitro was occluded by prior in vivo acute stress-induced, or prior in vitro glucocorticoid-induced, release of endocannabinoid. Acute stress also caused an increase in anxiety-like behavior that was attenuated by blocking CB1 receptor activation and inhibiting 2-AG synthesis in the BLA. Together, these findings suggest that acute stress causes a long-lasting suppression of synaptic inhibition in BLA neurons via a membrane glucocorticoid receptor-induced release of 2-AG at GABA synapses, which contributes to stress-induced anxiogenesis. We provide a cellular mechanism in the basolateral amygdala (BLA) for the rapid stress regulation of anxiogenesis in rats. We demonstrate a nongenomic glucocorticoid induction of long-lasting suppression of synaptic inhibition that is mediated by retrograde endocannabinoid release at GABA synapses. The rapid glucocorticoid-induced endocannabinoid suppression of synaptic inhibition is initiated by a membrane-associated glucocorticoid receptor in BLA principal neurons. We show that acute stress increases anxiety-like behavior via an endocannabinoid-dependent mechanism centered in the BLA. The stress-induced endocannabinoid modulation of synaptic transmission in the BLA contributes, therefore, to the stress regulation of anxiety, and may play a role in anxiety disorders of the amygdala.